Printreading for Welders (kèm CD) - Proctor Thomas E. (American technical publishers, 2004)
This book since its introduction has been the detail-oriented activities, which elicit critical thinking in the application of printreading principle. New industrial prints and activities build on this approach and further augment comprehension and learning.